Congestion in the Electricity Transmission System Redistributes Pollution across Long Distances - Erik P. Johnson; Juan Moreno-Cruz (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Electricity transmission redistributes environmental impacts across space. We exploit episodes of high electricity transmission system congestion to explore changes in ambient concentrations of air pollutants in the eastern United States. Reducing electricity system congestion decreases ozone and PM2.5 concentrations in New England and New York and increases them in the western portions of the Pennsylvania-New Jersey-Maryland electricity market and much of the Midwestern states. We quantify the health impacts of changes in environmental pollution induced by a reduction in congestion and find overall health losses in central states such as Illinois, Indiana, and Ohio and health gains in Atlantic.
Keywords: Q51; Q52; Q53; 330; electricity congestion; air quality; electricity transmission; health impacts